POSSIBLE INFLUENCE of FENOBARBIYAL ON EFFICIENCY OF THERAPY OF FUNGAL INFECTIONS - Leonova, I.S.; Padalko, V.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Fenobarbital was found out essentially not influencing morphology, death rate of cells and intensity of breath of cells culture. Fenobarbital can stimulate accumulation of ergosterol in cells of culture, changing their stress-stability. This fact can testify that long use of the preparations containing fenobarbital, at fungal infections can influence a course and treatment of diseases.